Cutting it in costume - Gibson, Thomasina; Covener, Alan (United Kingdom : Classroom Video, 2009)
'Clothes may make the man, but they really make the convincing dramatic character! Costume forms a crucial part of any stage production: get it right and it can say as much as the most eloquent soliloquy; get it wrong and it can distract from the best efforts of your production. This program explores the options available to students during the design process. Starting with a history of theatrical costume, the program goes on to explore the effects which can be created by using different materials, colours and patterns. Finally it discusses the role of the Wardrobe Supervisor, showing how students can make their drama work even more professional and convincing'--Container.
Presenter: Kate Balderstone.
Keywords: Costume design; Costume; Costume -- History